Tonic-clonic seizure after unrecognized unintentional dural puncture. (November 2020) - Taylor, C.R.; Mehdiratta, J.E.; Yurashevich, M.; Dominguez, J.E.; Habib, A.S.
Highlights: Major neurologic complications following dural puncture are rare events. Dural puncture can result in intracranial hypotension leading to seizure activity. Epidural blood patch after dural puncture may reduce the risk of some complications. Inexperienced headache assessment missed opportunity to diagnose etiology early. Communication breakdown delayed the diagnosis of post-dural puncture headache. Abstract: Patients who suffer an unintentional dural puncture have a high risk of developing a post-dural puncture headache. Other neurologic complications have been reported, but seizure is rarely seen. We present a case of a 21-year-old primigravida who experienced an unrecognized unintentional dural puncture that ultimately resulted in a tonic-clonic seizure from intracranial hypotension one week following the dural breach. Her trachea was intubated and she was transferred to the intensive care unit. Two epidural blood patches, performed by neuroradiologists, were needed before the patient experienced complete resolution of her headache. During the re-admission, she also experienced a pulmonary embolus which further lengthened her hospital stay.